Metabolic-Modulating and Antibacterial Nanoplatforms Improve Immunosuppression via Downregulating Glycolysis Pathway in Fusobacterium nucleatum -Infected Colorectal Cancer Therapy - Jingwen Ma; Yun Zeng; Xiaoye Wang; Yuan Liu; Dan Xiao; Bowei Zhou; Na Cai; Rong Qiang (ACS Applied Nano Materials, 2026)
Abstract Fusobacterium nucleatum (F.n.) infection is closely related to poor prognosis and high mortality in colorectal cancer (CRC) patients, promotes the proliferation and migration of CRC cells, induces inflammation, and creates an immunosuppressive tumor microenvironment. Compared with CRC cells not infected with F.n., F.n.-infected CRC cells exhibit greater glycolytic activity, considered as a beneficial metabolic change for establishing a symbiotic relationship between CRC cells and F.n. In this study, the classical glycolysis inhibitors 2-deoxy-d-glucose (2-DG) and tanshinone IIA (TAN IIA) were coloaded into zeolitic imidazolate framework-8 nanoparticles (DTZP NPs) to suppress F.n.-infected CRC growth. TAN IIA not only eliminated intratumoral F.n. but also acted as a chemotherapeutic drug against F.n.-infected CRC cells. DTZP NPs strongly inhibited both the F.n.-infected MC38 tumor model and the azoxymethane (AOM)/dextran sulfate sodium salt (DSS)-induced spontaneous CRC model by downregulating the NF-κB/HIF-1α/glycolysis pathway. DTZP NPs’ treatment improved the immunosuppressive tumor microenvironment, decreased the inflammatory levels in both serum and tumor tissue, and modulated the gut microbiota and its metabolites. In summary, we proposed combining anti-intratumoral F.n. with adjusting the tumor metabolism strategy, which could provide new insights into the treatment of F.n.-infected CRC in the future.